Influence Of Block Chain In Hrd Towards Employee Performance In Chennai City - K, Shruthi.; Kavitha, M. (Journal of Neonatal Surgery, 2025)
Block chain technology is starting to revolutionize human resource development (HRD) by providing creative ways to improve worker performance. This study examines how block chain technology may be used into HRD procedures including hiring, payroll administration, performance reviews, and training, highlighting how it can increase efficiency, security, and transparency. Block chain's decentralization of HR operations reduces fraud and administrative inefficiencies by guaranteeing secure credential authentication, automated contract enforcement using smart contracts, and tamper-proof personnel data. The research also looks into how employee engagement, trust, and productivity are affected by block chain-driven HR processes. Immutable performance monitoring and improved data security promote an equitable and merit-based workplace, which has a favorable effect on employee commitment and job satisfaction. A conceptual framework is put out to investigate the connection between employee performance and block chain-enabled HRD, taking into account mediating elements as technical adaptation and employee trust. Using a mixed-method approach, this study combines qualitative interviews with HR experts and workers from a range of sectors with quantitative surveys. It is anticipated that the results will give strategic advice for companies looking to use block chain technology for sustainable workforce development as well as empirical insights into the efficacy of this technology in HRD.